Surgical Outcomes of Cerebellopontine Angle Tumors in 48 Cases - Rahman, Md Atikur; Hafiz, Ahsan Mohammad; Islam, KM Tarikul; Mitra, Pijush Kanti; Mahmud, Ehsan; Barua, Kanak Kanti (Bangladesh Journal of Neurosurgery, 2020)
Background: Share our experiences with a series of surgical removal of cerebellopontine angle with retrosigmoid suboccipital procedure. Materials and Methods: It was a retrospective study of 48 patients (mean age, 45 years) with Cerebellopontine Angle tumors (predominantly acoustic schwannoma) who underwent surgical removal and one year post-operative follow up. Results: Hearing improvement about 50% of patient. Facial nerve function as measured by the House Brackmann system was recorded in all patients 1 year following surgery: 35% had a score of 1 or 2; 25% had a score of 3 or 4; and 8% had a score of 5 or 6. Rest of the patient full recover Two death occurred during this study. There was one cerebrospinal fluid leak, and two patients were diagnosed as having bacterial meningitis. Complete gross tumor removal was not achieved in five patients (10%). Two cases had wound infections. Conclusion: The retrosigmoid suboccipital procedure was used in our series for removal CPA tumors, and outcome was good in this series. Bang. J Neurosurgery 2020; 9(2): 117-220